Penguatan Kesadaran Bahaya Narkoba melalui Edukasi Interaktif bagi Siswa SMK Negeri 1 Pagelaran - Amaliyah, Dede Siska; Melinda, Hanna Septia; Majid Majid; Siti Komariah; Al-Aina Mardiah (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service activity was carried out to increase students' understanding of the dangers of drug abuse and its impact on academic achievement and the future of the younger generation at SMK Negeri 1 Pagelaran. The problem of low student awareness and limited access to accurate information about drugs was the main background for this activity. The community service program was designed using interactive socialization and education methods that included direct counseling, educational video screenings, group discussions, and the provision of supporting media in the form of leaflets as a means of reinforcing the material. The results of the activity showed an increase in students' knowledge and understanding regarding the risks of drug abuse, particularly its impact on decreased learning concentration, physical and mental health disorders, and weakened motivation and academic achievement. In addition, students showed high enthusiasm during the activity and were able to identify internal and external factors that can encourage and prevent involvement in drug abuse. This activity made a positive contribution to the school as a preventive effort and became the basis for the development of a sustainable and more comprehensive drug prevention program.